2013
DOI: 10.1071/ah12039
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians and their cameras: policy, ethics and practice in an Australian tertiary hospital

Abstract: Abstract.Medical photography illustrates what people would prefer to keep private, is practiced when people are vulnerable, and has the power to freeze a moment in time. Given it is a sensitive area of health, lawful and ethical practice is paramount. This paper recognises and seeks to clarify the possibility of widespread clinician-taken medical photography in a tertiary hospital in Australia, examining the legal and ethical implications of this practice. A framework of law, state Department of Health policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 13 publications
0
32
0
4
Order By: Relevance
“…Often, these images are stored in the same location that personal images are stored, which also provides ample opportunity for confidential images to surface during a casual conversation that is unrelated to patient care, a practice clearly at odds with ethical conduct (7). With the current prevalence of the practice of using smart phones as clinical cameras, the issues of proper clinical image storage on smart phones must be resolved and an alternative to smart phone bans must be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Often, these images are stored in the same location that personal images are stored, which also provides ample opportunity for confidential images to surface during a casual conversation that is unrelated to patient care, a practice clearly at odds with ethical conduct (7). With the current prevalence of the practice of using smart phones as clinical cameras, the issues of proper clinical image storage on smart phones must be resolved and an alternative to smart phone bans must be explored.…”
Section: Discussionmentioning
confidence: 99%
“…While the abusive use of clinical photographs has become an increasing preoccupation of health fund organizations [75], only 30% of patients worry about the future of their photographs [76], and our review reported that only slightly more than half of the authors encrypted their data. While 60% of specialists continue to store photographs of their patients in their personal cell phones [74,[76][77][78][79], one perspective could be to develop recourse to encrypt the medical image libraries [66].…”
Section: Discussionmentioning
confidence: 99%
“…The very simplicity of modern digital photography has resulted, in some cases, in a relaxation of the usually applied guidelines of informed consent 9. An unequal power balance could exist between health care professionals and patients who may feel coerced into consenting to digital photography 10. Taking photographs of at-risk and vulnerable populations requires greater ethical responsibility 11.…”
Section: Introductionmentioning
confidence: 99%